If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 16x + 15 = 8x + 33 Reorder the terms: 15 + 16x = 8x + 33 Reorder the terms: 15 + 16x = 33 + 8x Solving 15 + 16x = 33 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. 15 + 16x + -8x = 33 + 8x + -8x Combine like terms: 16x + -8x = 8x 15 + 8x = 33 + 8x + -8x Combine like terms: 8x + -8x = 0 15 + 8x = 33 + 0 15 + 8x = 33 Add '-15' to each side of the equation. 15 + -15 + 8x = 33 + -15 Combine like terms: 15 + -15 = 0 0 + 8x = 33 + -15 8x = 33 + -15 Combine like terms: 33 + -15 = 18 8x = 18 Divide each side by '8'. x = 2.25 Simplifying x = 2.25
| w-4/w-2+1=w-3/w+2 | | 7x+6/3-9=-12 | | -8n+4=-6n-10 | | x^3+4x^2+4x= | | 2y^2+2y-12=y^2-4y-12 | | -5(1+5x)=-120 | | 5x^2-9x=36 | | 3t-7=4t+3 | | 54/51 | | 3+5(x+6)=27+7x | | 3+1.5x+4=4x+2.5x | | 3x^3-36x-3=0 | | 2w^2-6w+4=w^2-w-6 | | 4y^4-4y=0 | | 9x^(4/3)-10x^(2/3)+1=0 | | 17=n-4 | | 5y-13=4(y-1) | | 3x^2+x-3=0 | | 10(4c-1)-4=38c+10 | | x1=-(-2/3)-5(2/15)-5(7/15)+2 | | 3/7-2/14 | | -1.25t+4=0.75(t-8) | | 6(y-2)=2y-24 | | 13n+2n=60 | | 91=-5n+4(7n-6) | | .25t+7=1 | | 21/4*32/3+5/6 | | 7n+2n=63 | | -7+42+35=21-35 | | 8x-6(2x-4)=2(-2x-12) | | 2(m+1.5)=1.5(2m+3) | | 8n+4=-6n-10 |